2020
DOI: 10.1002/ese3.835
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fuzzy control energy management strategy for fuel cell vehicle power system using a multi‐islandgenetic algorithm

Abstract: Energy storage system can be used to increase the fuel economy of fuel cell system (FCS). In this study, a new method was introduced for optimizing the energy management strategy (EMS) for fuel cell vehicle (FCV) to reduce fuel consumption. The membership function (MF) in fuzzy control is subjective; thus, 12 design variables in the input‐output MFs were selected using sensitivity analysis, and elliptical basis function neural network method was used to establish a high‐precision approximate model of FCV. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…A multi-island genetic algorithm was used to optimize the MFs and demonstrated optimized fuzzy control EMS in simulations of two EMSs under four driving cycles. The simulation results confirmed that the optimized fuzzy control EMS provided smoother and more stable output power from FCS, reducing hydrogen consumption by 8.4%, 1.1%, 5.1%, and 7.6%, respectively, compared to the original fuzzy control EMS [24]. Jibin et al proposed a parameter matching approach for a hybrid energy storage system based on a multi-objective optimization algorithm with a system simulation model in the loop designed by using an NSGA-II-type genetic algorithm.…”
Section: Introductionsupporting
confidence: 54%
“…A multi-island genetic algorithm was used to optimize the MFs and demonstrated optimized fuzzy control EMS in simulations of two EMSs under four driving cycles. The simulation results confirmed that the optimized fuzzy control EMS provided smoother and more stable output power from FCS, reducing hydrogen consumption by 8.4%, 1.1%, 5.1%, and 7.6%, respectively, compared to the original fuzzy control EMS [24]. Jibin et al proposed a parameter matching approach for a hybrid energy storage system based on a multi-objective optimization algorithm with a system simulation model in the loop designed by using an NSGA-II-type genetic algorithm.…”
Section: Introductionsupporting
confidence: 54%
“…The consumption of hydrogen fuel is applied relying on the optimal control theory to regulate the ratio of energy delivered by the integrated PEMFC Battery power system. Zhen Zhao, et al [20], proposed fuzzy control optimization of EMS for FCEV relying on a multi-island genetic algorithm. In 2021, Jiawen Li, et al [21], introduces a Largescale control system of multi-agent deep learning-based management strategy for energy control optimization of PEMFC.…”
Section: Related Workmentioning
confidence: 99%
“…With the ability to adjust the control according to the changing environment, enhance the robustness of the control system, anti-interference, etc. [11][12][13][14][15][16][17]. But its complex calculation will increase the amount of calculation of the control system, affect the stability of the system.…”
Section: Introductionmentioning
confidence: 99%